RAGAM KOSAKATA BAHASA ARAB DALAM PENAMAAN HOTEL DI SURABAYA - Kamal Yusuf; Qomarotul Lail Safrianti; Nailah Rofifah; Adam Nashirullah (An-Nas, 2022)
This study aims to explain the use of various Arabic vocabulary for hotel names in Surabaya. The method used is descriptive-qualitative method. The data was obtained from the android-based hospitality application, namely Booking.com and Traveloka.com. The data is collected, classified, analyzed, then concluded based on linguistic studies, namely linguistic characters, the use of sharia names, and the combination of Arabic with other languages. Based on linguistic characteristics, the names of hotels in Surabaya use singular nouns with a percentage of 89%, while the remaining 5 percent are in the form of verbs and 6% are in the form of Idhofah and plural. The names of hotels that use the word "sharia" in Surabaya have seven patterns, generally include the general name of the hotel then the type of accommodation and the addition of the word "sharia". Almost all hotels in Surabaya that use Arabic consist of one word and besides that, several hotels have their names combined with various languages, namely Indonesian, Javanese, and English